ChemInform Abstract: Hydrochalcogenation of Symmetrical and Unsymmetrical Buta‐1, 3‐diynes with Diaryl Dichalcogenides: Facile Entry to (Z)‐1‐(Organylchalcogeno)but‐1‐en‐3‐yne Derivatives. Issue 25 (5th June 2015) - Venkateswarlu, Cheerladinne; Chandrasekaran, Srinivasan
Abstract: The hydrothiolation and selenation reactions allow the stereoselective and regioselective synthesis of a wide range of enynes and butadienes.